Effect of high‐pressure homogenization on the sensory, nutritional and physical characteristics of mango nectar (Mangifera indica L.). Issue 11 (2nd September 2022) - Joly, Victoria; Brat, Pierre; Nigen, Michael; Lebrun, Marc; Maraval, Isabelle; Ricci, Julien; Forestier‐Chiron, Nelly; Servent, Adrien
Abstract: High‐pressure homogenization (HPH) was applied within a range of 300 to 1000 bar for 2 to 8 cycles. At constant dry matter (6.2%), pulp mass increased from 3.7 to 8%, indicating a change in particle organization. D90 varied from 197 to 20 μm depending on the pressure and number of cycles. The aggregation of particles, then destruction of the aggregates depending on the number of cycles, explained viscosity behavior. HPH delayed phase separation by an average 28.5 h. Sedimentation velocity was 10 times higher at 8 cycles than at 3 cycles, at 1000 bar. At 1000 bar, browning was observed, resulting from Maillard reactions, and was linked to the furan‐2‐pentyl content (10‐fold higher) and a 45% loss of carotenoids. This study will help in understanding changes induced in mango nectar by HPH and will be of use in developing processing technologies to preserve mango‐based products. Novelty impact statement: This study provides some additional scientific indications for understanding the subtility of HPH impacts in stabilizing mango nectar. The optimum pressure treatment for delaying phase separation (1000 bar, 3–6 cycles), i.e., reducing particle size and forming adequate re‐aggregation, also causes a Maillard reaction (2‐fold color difference, 10‐fold furan increase, etc.), hence browning through an increase in local temperature. It will therefore be necessary to find a compromise to limit degradation reactions caused by the process, and to guarantee greater consumer acceptance (phase separation and sensory quality).